Synchronization of Active Power Filter under Distorted Grid Conditions - Ikram Ullah (International Journal of Robotics and Control Systems, 2021)
Advancement in technology has resulted in increased use of electrical energy. The trend of using energy-saving appliances is also increased considerably. Harmonic currents have been increased in power systems due to the large-scale use of nonlinear loads. Shunt Active Power Filter (SAPF) is the most widely used technique for the compensation of current harmonics. Under adverse grid conditions performance of SAPF is affected badly. In this paper, a modified synchronous reference frame theory is proposed for current reference generation by incorporating an advanced phase-locked loop technique for the estimation of frequency and phase. The proposed approach results in an accurate extraction of reference current in the presence of various grid disturbances. Matlab/Simulink environment is used for evaluating the performance. The results achieved show excellent performance of the proposed technique in terms of reducing harmonics distortion and dynamic response. The total harmonics distortion of the compensated source current is reduced to a value well within the limits of the IEEE-519 standard.